Effects of aquatic exercises on upper limb physical function after a humeral shaft fracture – a time series analysis - Silva, Pedro A.C.; Santos, Eduarda H.; Cobbo, Paola; Miranda, Camila G.; Nampo, Daniel B.; Oda, Shigueo B.; Obara, Karen; Cardoso, Jefferson R. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Humeral shaft fractures account for 1.2% of all fractures in adults. Regardless of the treatment approach, the consequences of immobility can lead to decreased functional capacity in these individuals.Methods. This case report describes a 46-year-old male patient with a fracture of the greater tubercle and diaphysis of the humerus in the left limb (non-dominant) treated with 15 aquatic exercise sessions and five land-based sessions. The Disabilities of the Arm, Shoulder, and Hand Questionnaire (DASH) assessed physical function, Simulation Modeling Analysis (SMA) (autocorrelation, r, and significance) evaluated DASH measurements pre- and post-intervention, and the minimum clinically important difference (MCID) was reported. A MicroFet 2 HHD portable dynamometer measured muscle strength, while a manual goniometer assessed range of motion (ROM).Results. The MCID was reached in the DASH questionnaire, with an 18.3% improvement in physical function. The data analysed by SMA showed autocorrelation = –0.78, r = –0.87, and p = 0.01. There was an improvement in the ROM in all shoulder and elbow movements and an increase in the strength of the shoulder and elbow flexor muscles.Conclusions. Time series analysis with a slope of –2.25 each week predicted physical function. A score of zero on the DASH questionnaire indicated the absence of functional impairment and meant that the MCID was reached. Improvements in shoulder and elbow ROM and increased muscle strength were observed on the affected side.
Keywords: postoperative; linear models; humeral fractures; aquatic exercises; hydrotherapy